Adaptive admission control in real-time systems - Ferreira, André Filipe dos Santos (2009)
In real-time service provisioning platforms the existence of an efficient and flexible admission control mechanism is essential for providing quality of service in a reliable and stable way, avoiding congestion scenarios caused by indiscriminate and uncontrolled service request admission. The capability of modeling and regulating the rate of call acceptance, and provide service differentiation allow indirect control of the load submitted to the platform. This paper presents a service differentiated admission control solution that allows to limit and modulate the rate by which service requests are submitted into a service provisioning platform. The solution is focused on providing a fair level of bandwidth sharing among service classes, in a configurable and dynamic way so that it can adapt the distribution by which service requests are served. To sustain the design decisions of our solution, major scheduling disciplines and rate control mechanisms, some of them proposed recently, are studied and compared. The solution was submitted to unit and charge tests, whose results show its effectiveness and robustness.